2002
DOI: 10.1002/cncr.10862
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to enrollment in cancer clinical trials

Abstract: BACKGROUNDThe literature continues to report low rates of accrual to cancer clinical trials. Previous studies have examined principally physician‐related or patient‐related barriers. Clinical research associates (CRAs) have a unique perspective on enrollment that has been explored very little. This study sought the views of CRAs on barriers and facilitators to accrual.METHODSFocus groups were held at six of eight tertiary cancer centers in Ontario, Canada. Audiotapes of sessions were transcribed and subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 13 publications
2
63
0
Order By: Relevance
“…In the literature there is a differentiation between doctor, patient and system factors [14]. A review article differentiated between logistic problems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there is a differentiation between doctor, patient and system factors [14]. A review article differentiated between logistic problems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to better understand the barriers to Hispanic participation in cancer registries and, to some degree, clinical trial participation. Limited data found in existing literature suggest that key barriers to minority recruitment into clinical trials include lack of education and mistrust of research [3,4,5,6,7,8,9,10,11], researchers, and the medical system [4,7,8,9,10,11,12,13,14,15,16]. Among others are lack of health insurance [12,17,18,19], low income and indirect costs to participation [15,16,17,18,19,20], and age [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature review by Ford et al [25] has shown that perceived harm of clinical trial participation and fear are among the most frequently reported barriers that minimize clinical trial participation. Some promoters of clinical trial participation among minorities include provider incentives [5, 8, 9], altruism [3, 9, 13, 14, 26], and culturally relevant education about clinical trials [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was found that enrollment was low in clinical trials conducted by companies with ''bad press'' due to a corporation's reputation. When clinical research associates thought it worthwhile to survey their colleagues to identify the issues that encourage or discourage individuals to participate in corporate sponsored clinical trials, an important impediment was identified in the focus groups: negative media coverage can drop a study's accrual rate to zero [Grunfeld et al, 2002].…”
Section: External Indicatorsmentioning
confidence: 99%